The Role of Virtual Laboratory as an Interactive Learning Medium in Enhancing Student Motivation and Interest: A Systematic Literature Review - Muhammad Fadhil Khairullah; Tiara Dwi Saiva; Siti Nurlaili; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Applied Science and Technology, 2023)
The development of digital technology in education encourages the use of virtual laboratories as an interactive learning medium to overcome limitations of practical facilities and improve learning quality. This study aims to examine the effect of virtual laboratory use on student motivation and learning interest through a literature review method. The focus of this study is to analyze the results of previous research related to the effectiveness of virtual laboratories in creating interactive and meaningful learning. This study involved the analysis of 26 relevant scientific articles published between 2014 and 2023. The research stages included literature searches, selection based on inclusion criteria, content analysis, and synthesis of research results. The results of the study indicate that the use of virtual laboratories consistently increases student motivation and learning interest through interactive, visual, and flexible learning experiences published between 2014 and 2023. However, there are limitations such as dependence on technology and a lack of direct practical experience. Thus, virtual laboratories have great potential as an innovative learning medium that is effective in increasing student motivation and learning interest.